National Crime Surveys: National Sample, 1973-1983 ([Verlag nicht ermittelbar], 1984)
The National Crime Survey (NCS), a study of personal and household victimization, measures victimization for six selected crimes, including attempts. The NCS was designed to achieve three primary objectives: to develop detailed information about the victims and consequences of crime, to estimate the number and types of crimes not reported to police, and to provide uniform measures of selected types of crime. The surveys cover the following types of crimes, including attempts: rape, robbery, assault, burglary, larceny, and auto or motor vehicle theft. Crimes such as murder, kidnapping, shoplifting, and gambling are not covered. Questions designed to obtain data on the characteristics and circumstances of the victimization were asked in each incident report. Items such as time and place of occurrence, injuries suffered, medical expenses incurred, number, age, race, and sex of offender(s), relationship of offender(s) to victim (stranger, casual acquaintance, relative, etc.), and other detailed data relevant to a complete description of the incident were included. Legal and technical terms, such as assault and larceny, were avoided during the interviews. Incidents were later classified in more technical terms based upon the presence or absence of certain elements. In addition, data were collected in the study to obtain information on the victims' education, migration, labor force status, occupation, and income. Full data for each year are contained in Parts 101-110. Incident-level extract files (Parts 1-10, 41) are available to provide users with files that are easy to manipulate. The incident-level datasets contain each incident record that appears in the full sample file, the victim's person record, and the victim's household information. These data include person and household information for incidents only. Subsetted person-level files also are available as Parts 50-79. All of the variables for victims are repeated for a maximum of four incidents per victim. There is one person-level subset file for each interview quarter of the complete national sample from 1973 through the second interview quarter in 1980.